Mediated Electrochemistry to Mimic Biology's Oxidative Assembly of Functional Matrices. (2nd June 2020) - Li, Jinyang; Kim, Eunkyoung; Gray, Kelsey M.; Conrad, Christina; Tsao, Chen‐Yu; Wang, Sally P.; Zong, Guanghui; Scarcelli, Giuliano; Stroka, Kimberly M.; Wang, Lai‐Xi; Bentley, William E.; Payne, Gregory F.
Abstract: Biology uses diffusible oxidants to perform functions that range from signaling to matrix assembly, and these oxidation chemistries offer surprising selectivities. Here, it is reported that mediated electrochemistry can access the richness of such oxidation chemistries. Specifically, electrode‐imposed voltage inputs are used to locally generate oxidized mediators that can diffuse into polymer solutions and induce the formation of covalent bonds for the deposition and functionalization of hydrogels at the electrode surface. Depending on the mediator's redox potential ( E 0 ), it is possible to "gate" the voltage inputs to target specific residues (e.g., thiols or amines) and oxidation chemistries. Further, mediators of varying E 0 offer different reactivities and thus allow control of reaction‐diffusion rates to modulate the hydrogel's crosslink density and mechanical properties. Importantly, this mediated oxidation can be performed under physiologically relevant conditions to preserve labile biological functionalities (e.g., cell viability and protein function). Finally, it is demonstrated that protein fusion tags can be engineered to have "targetable" amino acid residues that enable protein function to be oxidatively conjugated to electrodeposited hydrogels. In summary, mediated electrochemistry can engage orthogonal oxidation chemistries to create functionalized matrices and thus mediated electrochemistry should add important capabilities to the electrofabrication toolbox. Abstract : Mediated‐electrochemistry is used to generate reactive and diffusible oxidants to induce the crosslinking and functionalization of polymeric hydrogels. This approach mimics biological mechanisms for oxidative matrix assembly as the reactive oxidants are generated with spatiotemporal control; selectively target different substituents; enable matrix assembly while preserving labile biological functionalities; and, in some cases, induce the formation of reversible linkages (e.g., disulfide bonds).